Release of phenolic compounds from cork stoppers and its effect on protein-haze. (April 2016) - Gabrielli, Mario; Fracassetti, Daniela; Tirelli, Antonio
Abstract: Cork stoppers contain low molecular weight phenols, mainly as ellagic tannin, whose role in the protein stability of white wine has been not elucidated. The release of cork phenols from cork granules, disks and stoppers of different quality classes (A and D) in synthetic wine was investigated as well as its effect on animal gelatin, lysozyme and wine protein. Amounts of cork phenolic compounds up to 115 and 179 µg/cm 2 were released within two weeks for best and worst quality cork disks, respectively, indicating the cork quality can strongly affect the phenolic compounds release. Similar trend was found for cork stoppers even if the concentration of phenolic compounds was lower (68 µg/cm 2 ). Protein-haze was observed in presence of both animal gelatin and lysozyme (50 mg/l) when the phenol level exceeded 30 and 9 mg/l, respectively, whereas no effect on wine protein was observed. This research suggests that even if the overall amount of phenolic compounds released from cork stoppers is low, protein-haze can be achieved when the bottle is stored horizontally and motionless due to the high phenols concentration close to the cork stopper. Highlights: Tannin release from cork products was investigated. The effect of tannin from cork on protein-haze formation was evaluated. Tannin release was mainly affected by cork quality. The haziness of white wine could be caused by cork tannin for bottled wine stored in laying down position and motionless.